Penentuan Prioritas Pengembangan Infrastruktur Kawasan Pesisir Pantai Jimbaran, Bali - Wikarna Aji, I Wayan Jagat; Saraswati, A. A. Ayu Oka; Mudra, I Ketut (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 11 No 1 (2024): April 2024DO - 10.24843/JRS.2024.v11.i01.p07, 2024)
Jimbaran Beach has various potentials that should be developed optimally, along with the increasing activities that take place at this coastal line. Fishing communities and tourism sector activities have proliferated for the last two decades. This, in consequence, requires both the provision of new infrastructures and the improvement of the inadequate existing infrastructures. This research aims to assess a list of prioritized infrastructures required by the fishing community and tourists of Jimbaran Beach. It uses a rationalistic quantitative approach and engages the Importance-Performance Analysis (IPA) technique. The study result shows that the following is a series of the most concerned infrastructures required by the Jimbaran Coastal Zone, including artificial tourist attractions, waste management, road network, culinary tourism, cultural tourism attractions, transportation facilities, parking lots, and pedestrian paths. Keywords: coastal area infrastructure; Jimbaran beach; development priorities   Abstrak Pantai Jimbaran memiliki beragam potensi yang patut dikembangkan secara optimal seiring dengan semakin beragamnya aktivitas yang terjadi di pesisir ini. Dalam dua dekade terakhir, kegiatan berkenaan sektor perikanan dan pariwisata telah tumbuh dengan pesat. Kondisi ini mensyaratkan pengadaan infrastruktur baru dan peningkatan kualitas infrastruktur yang ada. Penelitian ini bertujuan untuk mengkaji kebutuhan infrastruktur prioritas yang dibutuhkan, baik oleh masyarakat nelayan maupun wisatawan Pantai Jimbaran. Studi ini menggunakan pendekatan kuantitatif rasionalistik, dengan teknik analisis Importance-Performance Analysis (IPA). Hasil studi menunjukan daftar infrastruktur yang perlu diperhatikan kebutuhannya, termasuk atraksi wisata buatan, pengelolaan limbah sampah, jaringan jalan, wisata kuliner, atraksi wisata budaya, fasilitas transportasi, tempat parkir, dan jalur pedestrian.   Kata kunci: infrastruktur kawasan pesisir; pantai Jimbaran; prioritas pengembangan